PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PETERNAKAN KABUPATEN BIMA - Irvan Putra Ananta; Muhammad Badar; Jaenab Jaenab (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The aim of this research is to determine the influence of discipline and work motivation on the performance of employees at the Bima Regency Livestock Service so that it can provide thoughts to the leadership of the Bima Regency Livestock Service. This research is quantitative research. This type of research is associative with the population used in this research, namely all employees at the Bima Regency Animal Husbandry Service, totaling 173 respondents, consisting of 60 employees with PNS status (Civil Servants), 58 SK Honda employees and 55 honorary employees. The sample in this study was 33 employees, 12 civil servant employees, 11 SK Honda employees and 10 honorary employees. The sampling technique in this research used Stratified Random Sampling based on criteria. The research instrument used was a questionnaire with a Likert scale. The analytical tool used in this research uses multiple linear regression analysis using SPSS version 26. The results of this research are: 1) Work discipline has a significant effect on the performance of employees at the Bima Regency Animal Husbandry Service. 2) Work motivation has a significant effect on employee performance at the Bima Regency Livestock Service. 3) Work discipline and work motivation have a significant effect on employee performance at the Bima Regency Animal Husbandry Service.